Healing of delayed management of double traumatized incisors with complicated crown: Root fracture and apical pathosis - Abdullah M Alsaedan; Abdelhamied Y Saad (Wolters Kluwer Medknow Publications, 2017)
The present case report shows a 23-year-old male who was subjected to trauma in his maxillary right central and lateral incisors with crown and transverse apical third root fractures. Root canal therapy was started, but the patient did not complete it. After 6 years, the patient was subjected to another trauma on the same teeth and showed up after 3 weeks of the second trauma to continue his treatment. Clinical examination revealed that both incisors were sensitive to percussion and palpation with labial sinus tract and pus discharge through the open access cavity of the central incisor. Radiographic evaluation demonstrated root fracture of the central incisor with large radiolucency. Root canal treatment for both incisors and periradicular surgery was done. Histopathologic examination of the periapical lesion demonstrated tissue necrosis and fungal hyphae. Follow-up showed no symptoms with good healing. The treatment modality appears to be effective in dealing with delayed management of traumatized anterior teeth.